2021
DOI: 10.1080/21655979.2021.1964895
|View full text |Cite
|
Sign up to set email alerts
|

The up-regulation of miR-21 by gastrodin to promote the angiogenesis ability of human umbilical vein endothelial cells by activating the signaling pathway of PI3K/Akt

Abstract: Studies have shown that gastrodin has a protective effect on blood vessels. The purpose of this study was to investigate the influence of gastrodin on the angiogenesis ability of human umbilical vein endothelial cells (HUVECs) and its mechanism. We found that treatment of HUVECs with 10 µM and 25 µM gastrodin, and Vascular endothelial growth factor (VEGF) significantly upregulated the miR-21 expression in the cells. Meanwhile, gastrodin significantly increased the cell proliferation, migration and tube formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
0
12
0
2
Order By: Relevance
“…In our study, we found that gastrodin activated PI3K/Akt/Nrf2 pathway as well as reduced oxidative stress and inflammatory factors levels, thereby alleviating OGD/R-induced injury, which was in line with the finding held by Xu et al [ 18 ]. Compared with the results of Wang et al [ 39 ]. Our study further expands the application of gastrodin in retinal I/R injury by activating the PI3K/AKT/Nrf2 pathway.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In our study, we found that gastrodin activated PI3K/Akt/Nrf2 pathway as well as reduced oxidative stress and inflammatory factors levels, thereby alleviating OGD/R-induced injury, which was in line with the finding held by Xu et al [ 18 ]. Compared with the results of Wang et al [ 39 ]. Our study further expands the application of gastrodin in retinal I/R injury by activating the PI3K/AKT/Nrf2 pathway.…”
Section: Discussionmentioning
confidence: 64%
“…For example, sulforaphane activated Nrf2 through PI3K/Akt pathway, and improved the liver injury induced by arsenide [ 38 ]. Wang et al showed that gastrodin significantly activated the PI3K/Akt pathway and promoted angiogenesis of HUVECs [ 39 ]. Xu et al showed that Edaravone effectively protected the cell viability of H 2 O 2 -treated 661 W cells and improved retinal I/R damage through PI3K/Akt/Nrf2 pathway [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrated that VAP treatment generally dose-dependently promoted the viability, proliferation, colony formation, migration and invasion rates of ADSCs and the angiogenesis rate of HUVECs co-cultured with ADSCs, which would be partially abrogated when PI3K/Akt/HIF-1α pathway was blocked. Thus, we could speculate that the angiogenesis of HUVECs could be boosted through the activated PI3K/Akt pathway [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…HCAECs were cultured to the 3 rd passage, and cells reached 80% confluence. Firstly, different concentrations (5, 10, 20, and 30 μg) of EVs were co-cultured with HCAECs for 12 h, 24 h, 36 h, and 48 h under hypoxia, respectively; next, the CCK-8 assay was utilized to detect the cell proliferation ability, with the optimal treatment concentration determined as 20 μg and the optimal treatment time determined as 24 h. HCAECs were allocated into the following groups: (1) Hypoxia group; (2) Hypoxia + EVs group: treated with 20 μg EVs; (3) Hypoxia + GW group: treated with 20 μg GW4869; (4) Hypoxia + VEGF group: treated with 10 ng/mL VEGF [ 45 ] instead of EVs; (5) Hypoxia + EVs-si-NC group: treated with 20 μg EVs-si-NC; (6) Hypoxia + EVs-si-hnRNPU group: treated with 20 μg EVs-si-hnRNPU; (7) Hypoxia + EVs + si-NC group: treated with 20 μg EVs and transfected with si-NC; (8) Hypoxia + EVs + si-VEGF group: treated with 20 μg EVs and transfected with si-VEGF. In addition, HCAECs cultured in a CO 2 incubator at 37°C for 24 h under normoxia were used as the normal control (Normoxoia group).…”
Section: Methodsmentioning
confidence: 99%